TAVI-in-homograft (TiH): open transcatheter aortic valve replacement in calcified aortic homograft case reports - Gennari, Marco (J Cardiothorac Surg, 2019)
BACKGROUND: Redo surgery in patient who underwent aortic valve replacement with an aortic homograft can result technically challenging because of the massive calcification of the conduit. CASE PRESENTATION: We present a case of a patient who underwent open surgery on cardiopulmonary bypass assistance to implant a standard transcatheter aortic bioprosthesis through aortotomy in an off-label procedure and we discuss its safety and feasibility. CONCLUSIONS: The combination of open cardiac surgery and open trans-aortic implant of a transcatheter prosthesis may reduce the surgical risk shrinking the technical difficulties that the implantation of a standard surgical prosthesis would have given.